GoDonnie : definição e avaliação de uma linguagem de programação para comandar robô por programadores iniciantes com deficiência visual - Oliveira, Juliana Damasio (2017)
The general objective of this work was to define and evaluate a programming language to stimulate orientation and mobility (O&M) skills by people with visual impairment (VI). It is believed that by using a programming language to guide a robot in a virtual setting, the person with VI can better understand O&M skills. In this sense, it was definedthe programming language, which was called GoDonnie, and was based on the Logo language. A GoDonnie is run in a programming environment called Donnie, which provides soundbacks about running the robot. In addition, it has a 2D graphic simulator with a virtual robot, in which one can visualize the execution of the language commands, that is, the virtual robot sedeslocando in the scenario. This simulator allows the use by people with low vision, as well as serve as a resource to better visualize how the person who is blind is interacting with the robot in the environment. A GoDonnie has been evaluated to verify its usability. Evaluations were carried out which included visually impaired people and teachers of programming, without visual impairment. The results pointed out that GoDonnie has good usability, as well as helps the evelopment of O&M.